Implementation of BIBO Media (Bigbook) on Body Forms and Functions in Animals and Plants: Implementasi Media BIBO (Bigbook) pada Materi Bentuk dan Fungsi Tubuh pada Hewan dan Tumbuhan - Yurhaida Yurhaida (International Journal of Technology Vocational Education and Training, 2022)
The essence of a learning process is the interest of students to follow the learning process comfortably. This interest is called students' motivation, desire, and willingness to follow the learning process. Therefore, to increase the learning motivation of fourth grade students of SD N 01 Sitiung on the material of Body Shape and Function in Animals and Plants, BIBO (Big Book) media was used. This research was conducted through 2 cycles in which each cycle uses an observation sheet and each end of the cycle is taken value. After the learning process in cycle I and cycle II using BIBO media (Big Book) there is an increase in student learning motivation which is seen from the negative activity of students which is greatly reduced in cycle I 22.57 % decreased to 7.83 % in cycle II and activity positive increased from cycle I 61.74 % in cycle II to 90.32 %. Student learning outcomes also increased from an average of 78.39 at cycle I to 83.87 at the end of the cycle and student learning completion increased from 77.41 % to 90.32 % at the end of the cycle. Based on these results, it can be concluded that the use of BIBO media (Big Book) can increase the learning motivation of students of class IV SD N 01 Sitiung on the material The shape and function of animal and plant bodies.